Interpersonal violence against children and youth - Lim, Hyeyoung, 1973- (Lexington Books, 2022)
"Pulling together researchers, practitioners, and educators from around the world, this book addresses the various practices and efforts different countries use to protect children and prevent interpersonal violence"--